Analisis Kebutuhan Kurikulum: Upaya Meningkatkan Mutu Pendidikan - Putri, Marzhela M.; Nur, Ahmad; Hariani, Farida; Saleh, Sirajuddin (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The curriculum plays an important role in determining the direction and quality of education. This study aims to analyse curriculum requirements in an effort to improve the quality of education in Indonesia. The method used is a qualitative approach with a literature study design through an analysis of various scientific sources, education policies, and research results related to curriculum development. The results of the study show that a curriculum that is adaptive to student needs and developments over time has a significant effect on the effectiveness of learning. A relevant curriculum encourages teacher innovation, contextual learning, and the integration of technology in the teaching and learning process. The discussion also emphasises the importance of collaboration between the government, schools, and the community to support the implementation of a sustainable curriculum. In conclusion, periodic curriculum updates are necessary to ensure that education in Indonesia remains relevant and capable of responding to global challenges.